Relationship Between Family Influence, Job Satisfaction, and Organizational Commitment of Non-Family Employees: HR Practices as a Mediating Variable - Yuwono, Aylinda; Agustiono, Agustiono (The Graduate School of Sahid University, 2025)
This research is conducted to examine the relationship between family influence, HR Practices, job satisfaction, and organizational commitment. Data is collected through questionnaire, which is distributed to 100 non-family employees from 50 family SMEs in Universitas Ciputra (UC) Family Business Community. Two non-family employees are taken from each family SMEs as the representative of population. Samples are determined purposively with the criteria of non-family employees that work at least three years in family SMEs that owns 1-19 employees (small scale) or 20-99 employees (medium scale). Data is analysed using Structural Equation Modeling – Partial Least Square (PLS-SEM) with the help of SmartPLS version of 3.2.8 to know the direct and indirect effect of independent variable towards dependent variables. Independent variable is family influence that holds the power, experience, and culture aspect (F-PEC). Dependent variables refer to HR Practices, job satisfaction, and organizational commitment. Mediating roles of HR Practices and job satisfaction are also examined in this research. The path analysis results to the acceptance that family influence affects HR Practices (sig. value = 0.000), HR Practices affect job satisfaction (sig. value = 0.000), HR Practices affect organizational commitment (sig. value = 0.000), and job satisfaction affects organizational commitment (sig. value = 0.000). There are also confirmation on mediating roles of HR Practices between family influence and job satisfaction (sig.value = 0.000), mediating roles of HR Practices between family influence and organizational commitment (sig. value = 0.001), and mediating roles of job satisfaction between HR Practices and organizational commitment (sig. value = 0.001). All of hypotheses are accepted and inclined to be an accepted synthesized research.